PHYSIOLOGICAL AND BIOCHEMICAL EXPRESSIONS OF A DETERMINATED GROWTH COMMON BEAN GENOTYPE (Phaseolus vulgaris L.) TO WATER DEFICIT STRESS PERIODS - A. D. Sánchez-Reinoso; G.A. Ligarreto-Moreno; H. Restrepo-Díaz (Journal of Animal and Plant Sciences, 2018)
Climate change has had a major impact on agriculture, affecting rainfall patterns. This study was undertaken to understand the effect of different water deficit periods on the physiological and biochemical responses of ʻICA-Cerinzaʼ plants subjected to four water deficit periods (0, 5, 10 and 20 days). Sixty four1.5-L pots with one plant in each pot were arranged in a completely randomized design. Thirty-two pots watered with daily irrigation dose of 100% evapotranspitation (ETo) needs through the experiment (Control). The other 32 pots were irrigated with 50% ET (water deficit). The lowest relative water content (RWC) values were observed at the end of the 10- and 20-day deficit periods (~73 and ~30%, respectively). Photosynthesis rate (Pn), stomatal conductance (gs), chlorophyll and fluorescence ratios decreased in all deficit treatments. However, the effect was more severe in plants subjected to 20 days under water deficit, where Pn and the Fv/Fm ratio decreased about 40% compared to control plants (Pn = 9.6 µmol·m-2·s-1 and Fv/Fm = 0.52 in deficit vs. Pn = 16 µmol·m-2·s-1 and Fv/Fm = 0.79 in control plants). The electrolyte leakage, leaf carotenoids, malondialdehyde (MDA) and proline were higher in plants under prolonged (20 days). Results obtained suggested that ‘ICA-Cerinza’ plants could not adapt well and to landscaping situations where periods of extreme drought can be expected, since leaf gas exchange properties and membrane stability are seriously affected, which can have a negative effect on yield.
Keywords: lipid peroxidation; leaf gas exchange; proline; chlorophyll fluorescence; drought